A individuação segundo o projeto ontogenético de Gilbert Simondon: uma filosofia da informação - Souza, Diego Paim de (2024)
This research examines the role of the notion of information in Gilbert Simondon's philosophy of individuation. The aim is to elucidate how the concept of information underpins Simondon's philosophical project to develop a new theory of individuation. Initially, the paper situates Simondon's philosophy within the context of French philosophy, highlighting his method based on the realism of relations. It then explores Simondon's proposal for a philosophy of individuation that explains the processes of determination without presupposing predefined terms, thereby subverting Aristotelian hylomorphism. According to Simondon, the individuated state is merely one phase of being, coexisting with a pre-individual phase that accompanies all processes of determination. The study also connects this notion to pre-Socratic philosophy, which emphasizes processes, and distinguishes Simondon's view by considering pre-individual being as a metastable domain. The third chapter analyzes how Simondon employs the concept of information to explain the changing phases of being and the formation of each individual. By contextualizing the philosophy of information in the 20th century, it identifies how Simondon redefines the cybernetic conception of information, understanding it as that which initiates and guides the emergence of a new domain of reality from the tension between different fields.